The legal authenticity of the electronic contract In the Algerian legislation - Hamoud, Melissa (Journal of Human Sciences, 2021)
The technological development has led to the conclusion of most transactions by electronic means including commerce, and what has made the traditional means of proof and organized by the legislator in a writing, certificate, recognition, oaths, proof, experience  and overview, does not imitate the technological boom and powerless to prove the rights. Which necessitates the need to find effective means of electronic evidence corresponding to the nature of legal acts and contracts executed using modern technical means, in order to establish and demonstrate in court including electronic writing, email and electronic signature, and lawmakers have stipulated that proof of email esteem must be clear and unencrypted.